Emerging medium-scale tenant farming, gig economies, and the COVID-19 disruption: The case of commercial vegetable clusters in Ethiopia - Minten, Bart; Mohammed, Belay; Tamru, Seneshaw (Springer, 2020)
Driven by the fast spread of private irrigation pumps, there has been a rapid expansion of intensive vegetable cultivation in the central Rift Valley in Ethiopia, making it the most important commercial vegetable production cluster in the country. Supporting that “quiet revolution” has been an inflow of migrant laborers—paid through daily, monthly, or piecemeal contracts, with few employment benefits attached to them—and a gig economy as widely used contractors organize, among others, mechanized land preparation, the digging of wells and ponds, seedling propagation, and loading of trucks. Almost 60% of the irrigated area is cultivated by medium-scale tenant farmers relying on short-term rental contracts. It seems that gig economies characterized by flexible contract arrangements implemented by outside contractors, which are increasingly fueling sophisticated sectors in developed countries, are important in these commercial agrarian settings in Africa as well. We further find that the COVID-19 pandemic has led to significant disruptions of this model, as seen by more limited access to services and the unavailability or high price increases in factor markets, especially for labor, and large but heterogenous price changes in output markets.